The effectiveness of family-based empowerment on changing the emotional atmosphere of the family and prevention of addiction in adolescents with substance-dependent parents - Rahbari Ghazani, Nasrin; Hajloo, Nader; Aghajani, Seyfollah (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the effectiveness of family empowerment based on socio-emotional learning on changing the emotional atmosphere of the family and prevention of addiction in adolescents with substance dependent parents. Methods: The method of the present study was quasi-experimental with pre-test-post-test design and control and follow-up group. The statistical population consisted of adolescents with substance dependent parents who had referred to drug addiction treatment centers in Tabriz. 30 of them were sampled in a targeted and accessible manner and were randomly assigned to the experimental and control groups. Research data were collected using the Nordgah Fard Family Emotional Atmosphere Questionnaire (1994) and the Mousavi et al. Addiction Tendency Scale (2008) and analyzed by repeated measures analysis of variance. Results: The results of the present study showed that family empowerment is effective on changing the emotional atmosphere of the family and prevention of addiction in adolescents with substance dependent parents and this effectiveness is stable in quarterly follow-up. Conclusion: According to the results of the present study, it can be concluded that family empowerment based on socio-emotional learning is one of the effective therapies on the emotional atmosphere of the family and addiction prevention.